Pertussis epidemiological surveillance and immunization history in children under five years in a megacity in China from 2019 to 2023 - Yang Liu; Jing Chen; Ning Yao; Xiaoxiao Hu; Nian Yu; Qing Wang; Jiawei Xu (Human Vaccines & Immunotherapeutics)
To analyze the epidemiological characteristics and influencing factors of pertussis in children under five years in Chongqing from 2019 to 2023, providing scientific evidence for further prevention and control. The epidemiological characteristics of pertussis cases in children under five years and vaccination history with pertussis-containing vaccines were described, and the influencing factors and cumulative risk of disease onset after vaccination were analyzed using the Cox proportional hazards regression model. From 2019 to 2023, a total of 4,135 pertussis cases were reported in children under five years in Chongqing, with cases occurring predominantly between April and August. Infants under 1 year accounted for the highest proportion of cases at 66.82% (2,763/4,135); the annual reported incidence was higher in boys (141.26/100,000) than in girls (122.09/100,000). Over half of the cases, 59.78% (2,472/4,135) had received at least one dose of a pertussis-containing vaccine, and there were significant differences in vaccination history among different age groups (χ2 = 483.248, p < .01). Cox’s regression analysis indicated that the total number of doses received (p < .01) was an influencing factor for the interval between vaccination and disease onset. The hazard ratios (HRs) for three doses, two doses, and one dose were 0.182 (95% CI: 0.138–0.241), 0.485 (95% CI: 0.359–0.654), and 0.315 (95% CI: 0.233–0.425). Young children, including infants and preschool-aged children, were still a high-risk group for pertussis infection in Chongqing. It is recommended to administer an additional dose of Diphtheria-Tetanus-Pertussis vaccine (DTaP) vaccine to preschool children aged four to six in China.